2019
DOI: 10.1016/j.jcms.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the cause of late deformity following fronto-orbital remodelling for metopic synostosis using 3D CT imaging

Abstract: Late deformity/indentation is well-recognised following fronto-orbital remodelling (FOR) for metopic synostosis. We hypothesise that if damage to temporalis muscle was a contributor, thickness of soft tissue and bone in the affected area would be reduced.Soft tissues and bone were separately segmented and 3D reconstructed from CTs of 8 patients 1.5-18 years post-FOR performed at 16±2 months for metopic synostosis and from 8 agematched controls. Soft tissue (taken as proxy for temporalis muscle) and bone thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…19 It is this component that has been shown to have soft tissue and bony elements with thinning of both. 3 The present study strongly supports the theory that the soft tissue contribution to this component of LDD is the absence of the superior elements of temporalis from their normal position. This possibility has been raised before but discounted on the evidence of parental assessments of muscle location by palpation during their children's jaw movements.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…19 It is this component that has been shown to have soft tissue and bony elements with thinning of both. 3 The present study strongly supports the theory that the soft tissue contribution to this component of LDD is the absence of the superior elements of temporalis from their normal position. This possibility has been raised before but discounted on the evidence of parental assessments of muscle location by palpation during their children's jaw movements.…”
Section: Discussionsupporting
confidence: 88%
“…A previous study 3 demonstrated thinning of bone and soft tissue in the most affected area, the latter being attributed to absence of the upper elements of temporalis from their usual location. Possible explanations included per-operative damage to the muscle’s blood supply, 4,5 its innervation 6 and/or its fatpads, 7,8 inadequate muscle resuspension or its subsequent retraction 9,7 and, finally, interference with a previously undescribed childhood expansion of the muscle’s origin.…”
mentioning
confidence: 78%
“…The absence of these superior elements may also contribute to its bony component by the removal of the muscle's normal osteogenic stimulus (Rodriguez-Florez et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The investigation was prompted by a previous study (Rodriguez‐Florez et al, 2019) into the late‐developing deformity that can complicate reconstructive operations carried out between 6 and 18 months of age for metopic synostosis (van der Meulen et al, 2008; Wes et al, 2014) that identified the absence of temporalis in the area normally occupied by its superior elements as the prime contributor to its soft tissue component. We hypothesized that this deformity (which typically becomes apparent some 3–4 years post‐surgery) was the consequence of surgical interference (the operations involve detachment and later re‐attachment of temporalis) with a previously undescribed childhood upward extension of the muscle by operations performed between 6 and 18 months of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation